A photoluminescent thermometer made from a thermoresponsive tetranuclear gold complex and phosphor N630. Issue 44 (4th November 2021) - Xu, Wen-Di; Yan, Jia-Jun; Feng, Meng-Yao; Li, Hai-Yan; Young, David James; Ren, Zhi-Gang
Abstract : Au/P/S complex showed temperature-dependent PL emission related to the changing of Au–Au interaction. Thermochromic devices were prepared via the mixing of this complex with phosphor N630. Abstract : Reaction of [(3-bdppmapy)(AuCl)2 ] with NaHmba (3-bdppmapy = N, N ′-bis-(diphenylphosphanylmethyl-3-aminopytidine, H2 mba = 2-mercaptobenzoic acid) resulted in a new tetranuclear Au/P/S complex [(3-bdppmapy)2 (AuHmba)3 (AuCl)] (1 ). Upon excitation at 370 nm, 1 exhibited solid state, room temperature, green fluorescent emission (QY = 4.7%, τ = 2.58 ns) which was significantly enanced at lower temperatures due to strengthening of the Au–Au interaction. Different ratios of 1 with phosphor N630 in PMMA were used to make thermochromic photoluminescent films and fibres that could be fabricated into an optical thermometer sensitive over temperature ranges 80–300 K and 300–370 K.